Potential of Mitochondrial Genome Editing for Human Fertility Health - Fu, Lin; Luo, Yu-Xin; Liu, Ying; Liu, Hui; Li, Hong-zhen; Yu, Yang (Frontiers in Genetics, 2021)
Mitochondrial DNA (mtDNA) encodes vital proteins and RNAs for the normal functioning of the mitochondria. Mutations in mtDNA leading to mitochondrial dysfunction are relevant to a large spectrum of diseases, including fertility disorders. Since mtDNA undergoes rather complex processes during gametogenesis and fertilization, clarification of the changes and functions of mtDNA and its essential impact on gamete quality and fertility during this process is of great significance. Thanks to the emergence and rapid development of gene editing technology, breakthroughs have been made in mitochondrial genome editing (MGE), offering great potential for the treatment of mtDNA-related diseases. In this review, we summarize the features of mitochondria and their unique genome, emphasizing their inheritance patterns; illustrate the role of mtDNA in gametogenesis and fertilization; and discuss potential therapies based on MGE as well as the outlook in this field.